PENGARUH RASIO LIKUIDITAS, RASIO PROFITABILITAS, RASIO SOLVABILITAS, RASIO AKTIVITAS, DAN RASIO PERTUMBUHAN TERHADAP FINANCIAL DISTRESS. - Adhiyudho , Adhityo Krisno; Sufiyati, Sufiyati (Jurnal Paradigma Akuntansi, 2024)
This Research aim to know if there are correlation between liquidity ratio, profitability ratio, leverage ratio, activity ratio, and growth ratio to financial distress that happened on manufacturing company that the company already listed in Indonesia Stock Exchange during 2018 – 2020. Sample was chosen with purposive method and the data that was chosen to be research data is consist of 31 companies. Data that been used in this research is process with Eviews 12 and Microsoft Excel 2019. The research shows that liquidity, profitability, leverage, and activity ratio show significant influence on financial distress and growth ratio doesn’t have significant influence on financial distress. The implication on this research is that management should have be cautious when using debt and maximising the use of asset to prevent companies to enter the state of financial distress.